The Motive "Locative" in the Names of Medicinal Plants (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is devoted to the analysis of the nomination of some medicinal plants in three languages with different structures. The study examines the etymological features of plant names that explain the choice of the motive for their designation. A comparative analysis of the French, Russian and Uzbek languages is carried out in order to identify the linguacultural features associated with the perception and classification of plants in different peoples.